The new winter rye variety ‘Zilant’ with broad adaptability - М. L. Ponomareva; S. N. Ponomarev; G. S. Mannapova; L. F. Gilmullina; L. V. Ilalova; G. S. Vafina (Зерновое хозяйство России, 2021)
The purpose of the current work was to develop a highly productive winter rye variety for bakery with improved resistance to a complex of unfavorable factors and broad adaptability. The breeding work on the rye variety ‘Zilant’ was conducted in the Tatarsky Research Institute of Agriculture FRC of the Kazan Scientific Center of RAS in 2005–2015. The study of the variety in the Competitive Variety Testing was carried out in 2016–2019, in comparison with the standard varieties ‘Radon’ and ‘Tantana’. There has been presented a detailed characteristics of the variety ‘Zilant’ in terms of economically valuable indicators and adaptive potential according to grain productivity. The winter rye variety ‘Zilant’ formed the largest productivity on average for 4 years (50.2 hwt/ha) and produced high grain quality (229 s of a falling number and 647 u.a. of amylogram height, versus 224 s of a falling number and 625 u.a. of amylogram height of the standard variety ‘Radon’). The variety ‘Zilant’ has a dominant-monogenic type of short stems, strong short straw (on 14–13 cm lower than that of the standards). The variety possesses the same degree of field resistance to rust infections and ergot, resistance to powdery mildew as the standard variety ‘Radon’. There was determined that the rye variety ‘Zilant’, on average over the years of trials, was characterized by a significantly higher productivity (50.2 hwt/ ha, НСР05 = 1.5 c/ha) compared to the control, had a good combination of adaptability (bi = 1.149) and stability (Ϭd2 = 3.17). These advantages of the variety are provided by resistance to unfavorable environmental conditions, the formation of a denser cenosis, field resistance to diseases, and a short non-lodging stem. The rye variety ‘Zilant’ produced grain with high baking qualities, corresponding to the 1st class of standards for grain and flour. The variety was responsive to improving growing conditions, showed less response to stress factors and was adapted to a wide range of environmental conditions.